Proceedings of the 9th International Conference on Neural Information Processing, 2002. ICONIP '02. 2002
DOI: 10.1109/iconip.2002.1201915
|View full text |Cite
|
Sign up to set email alerts
|

Constructing bifurcation diagram for a chaotic time-series data through a recurrent neural network model

Abstract: The Bifurcation Diagram (BD) of a given dynamical system gives the idea of the behaviour of one of the outputs of that system with different values of one of the control input parameters keeping all the other input parameters constant. It also gives the idea of iterative behaviour of the system for the particular input conditions. Plotting the BD through the mathematical models is popular in control / chaos theory domain. In this work, a methodology to construct the BD from the available time-series data using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Most real-world processes as observed in [24] often have rich array of Bifurcation Diagrams and attractors. However, the Hénon map which has been selected as a model for processes has a relatively simple attractor.…”
Section: Controlling a Chaotic Process By Driving The System Towards mentioning
confidence: 99%
See 1 more Smart Citation
“…Most real-world processes as observed in [24] often have rich array of Bifurcation Diagrams and attractors. However, the Hénon map which has been selected as a model for processes has a relatively simple attractor.…”
Section: Controlling a Chaotic Process By Driving The System Towards mentioning
confidence: 99%
“…1, when trained on the time-series data of a chaotic system can be used to predict either the next one step or several steps in a recursive mode [23,24]. It is also known that most RNN architectures have a capability to suppress noise.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high temperatures, huge electrical arcs with varying currents, multiple chemical reactions and the fact that a large mass always remains inside the furnace, compared to one which is periodically tapped, makes it a complex and difficult to model process. In [11] it has been shown that the working of SAF can be chaotic in nature, based on the calculated value of the one of the Lyapunov exponents turning out to be positive for one of the output variables evolving in time.…”
Section: Introductionmentioning
confidence: 99%